EXPLORATION OF CHARACTER EDUCATION PERSPECTIVE OF LIVING VALUE EDUCATION: A CASE STUDY ON TPA ANWAR RASYID YOGYAKARTA - Muh. Akbar Patty; Taufiqurahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research explores character education at TPA Anwar Rasyid Yogyakarta from the perspective of Living Value Education (LVE), and analyzes the impact on students' character development. This research focuses on analyzing the learning process that contains positive values in the curriculum implementation, which includes classroom learning activities, educator and student interactions, and the application of values in daily activities. This research uses a qualitative approach with a case study type, data collected through a process of semi-structured interviews, non-participatory observation, and document analysis. The informants of this research consisted of TPA teachers, students, and parents to obtain in-depth information. The data analysis technique used the analysis model of Miles & Huberman, which includes data reduction, data presentation, and conclusion drawing, as well as data triangulation. The main findings of this study show the integration of universal moral values with a religious approach that supports students' character holistically. Character education in TPA includes strengthening three main aspects, namely cognitive (knowledge of values) through the study of the Qur'an and kitab, affective aspects (feelings and emotions about values) through storytelling, role playing, and self-reflection approaches, and psychomotor aspects (actions of applying values) through self-habituation activities. This character education has a significant impact in shaping students' morals and ethics, active participation of santri in every learning activity shapes their social skills, self-awareness, and academic achievement. The implications of this study include the development of a more integrated curriculum, the importance of parental involvement, and the development of a comprehensive character education model.